Fear-of-failure and cultural persistence in youth Entrepreneurship. Comparative analysis: Greece versus Germany - Tubadji, Annie; Dietrich, Hans; Angelis, Vasilis; Haas, Anette; Schels, Brigitte (Journal of Small Business and Entrepreneurship, 2021)
This paper explores the sensitivity of youth’s fear of failure to local culture, in terms of its persistence across space and its change (hysteresis) in times of economic shocks, which renders entrepreneurship a very dubious tool for tackling youth unemployment especially in times of crisis. We focus on youth in Germany and Greece which are culturally and economically very different countries. Data from the Global Entrepreneurship Monitor (GEM) provides a pooled cross-section for the period 2003–2010. We address the data using a probit model with year fixed effects. Regarding the influence of personal fear-of-failure, we find that youth between 15 and 24 years of age are less entrepreneurial in both Greece and Germany, while the 25–34 years old young adults in Greece are already at the same entrepreneurial level as an average adult. Our findings also support existing gender differentials in both countries, which generally phase out among young people. Yet, country differences in perceptions have the greatest impact on entrepreneurial propensity. Regarding the local cultural characteristics, there is evidence of cultural embeddedness and cultural persistence effects especially among youth between 15 and 24 years of age which makes entrepreneurship an unsuitable tool for handling youth unemployment for this age group.<br
Keywords: Entrepreneurship; age differentials; gender disparities; embeddedness; cultural persistence; Greece; Germany